2014
DOI: 10.1111/jop.12213
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of matrix metalloprotease‐2 and matrix metalloprotease‐9 in the disks of patients with temporomandibular joint dysfunction

Abstract: Purpose: Matrix metalloproteases (MMPs) are tissue-remodeling enzymes that function during the remodeling process, such as in immune-inflammatory diseases. Metalloprotease-2 (MMP-2) and metalloprotease-9 (MMP-9) are gelatinases that degrade several types of extracellular matrix collagen. It is hypothesized that in temporomandibular joint (TMJ) dysfunction, MMP-2 and MMP-9 expression levels may be elevated. Therefore, the objective of this study is to determine the association of MMP-2 and MMP-9 expression with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Our previous study demonstrated polymorphism of MMP1 promoter could increase the susceptibility to TMJ OA (14). The elevation of MMP2 was also revealed in TMJ displacement disks (15). Overexpression of MMP1 or MMP2 in synovial fluid is considered as a biochemical marker for TMJ OA (16,17).…”
Section: Discussionmentioning
confidence: 98%
“…Our previous study demonstrated polymorphism of MMP1 promoter could increase the susceptibility to TMJ OA (14). The elevation of MMP2 was also revealed in TMJ displacement disks (15). Overexpression of MMP1 or MMP2 in synovial fluid is considered as a biochemical marker for TMJ OA (16,17).…”
Section: Discussionmentioning
confidence: 98%
“…ECM degradation requires the action of secreted or membrane MMPs, which are zinc-dependent endopeptidases capable of degrading ECM components, including collagens and proteoglycans ( 44 ). MMP-9 degrades denatured collagen II, which is initially cleaved by activated MMP-1, and additionally degrades noncartilage collagens such as collagen IV and collagen V ( 45 ). Notably, MMP-9 is able to degrade the core protein aggrecan ( 46 , 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1. Studies that fit the inclusion criteria and published within the past 10 years [11,[13][14][15][16][17]. Anterior disc displacement with reduction (ADDwR); anterior disc displacement without reduction (ADDwoR); matrix metalloproteinases (MMP); temporomandibular joint (TMJ).…”
Section: Discussionmentioning
confidence: 99%
“…They are a family of 26 endopeptidases that degrade collagen, gelatin, proteoglycans, and other ECM components, and they are regulated at the level of their gene expression (cytokines, growth factors, hormones, and others), posttranslational activation, and endogenous inhibition (tissue inhibitors of metalloproteinases [TIMP]) [8,10]. As inflammation occurs, however, processes involving these enzymes shift from physiological to pathological, and MMP activity results in excess tissue breakdown and damage [11].…”
Section: Introductionmentioning
confidence: 99%